Onestop Solution Healthcare Distribution Service Perusahaan Pedagang Besar Farmasi (PBF) Distributor Healthcare PT Jagat Pharma Abadi - Patra Batam Prima; Deni Erlangga; Hasby Aprilian; Andri Subyakto (Jurnal Syntax Admiration, 2024)
The healthcare industry in Indonesia is experiencing rapid growth, which has triggered an increase in the need for efficient and effective health product distribution services. Pharmaceutical Wholesaler Companies (PBF) such as PT. Jagat Pharma Abbadi plays an important role in distributing health products from manufacturers to pharmacies and drug stores. This study aims to analyze the strategic planning of "OneStop Solution Healthcare Distribution Service" from PT Jagat Pharma Abadi in improving the efficiency of pharmaceutical product distribution. This study uses a qualitative research method with a case study approach. The data collection techniques in this study are literature studies, interviews and company documentation. The data analysis technique used in this study is thematic analysis. The results of the study show that the strategic planning of "OneStop Solution Healthcare Distribution Service" from PT Jagat Pharma Abadi uses the External Factor Evaluation Matrix (EFE), Internal Factor Evaluation Matrix (IFE), and Competitive Profile Matrix (CPM). PT JPA will adjust marketing activities with both pull and push strategies, using two concepts, namely: make to stock and make to order to reduce the risk of slow-moving products, dead goods, and the threat of substitution. PT JPA must be able to manage inventory according to estimates from the marketing team and remain flexible and dynamic to face competitive dynamics.